(untitled) (Indonesian Contemporary Nursing Journal (ICON Journal), 2025)
Aims: This research aims to analyze the effectiveness of Kenali Promprev’s implementation in achieving the effectiveness level of Prolanis visits at FKTP in Bulukumba Regency in 2023. Kenali Promprev is an educational program delivered through direct meetings, Focus Group Discussions, and feedback via WhatsApp groups focusing on promotive and preventive actions such as Health History Screening. Methods: The method used is a descriptive quantitative and Mann-Whitney test, utilizing secondary data from Prolanis participant visits to FKTP in 2023. The data is then compared to evaluate the improvement in the effectiveness of Prolanis visits before and after the implementation of Kenali Promprev in Bulukumba Regency in 2023. Results: The findings indicate that the implementation of Kenali Promprev starting July 2023 has resulted in increased registration of Prolanis participants by 1,005 (70%), 1,123 (127%) participants conducting visits, and 570 (679%) controlled Prolanis participants. Conclusion: Consequently, the effectiveness level of Prolanis visits at FKTP has improved, with potential implications for enhancing the Controlled Prolanis Participant Ratio, a key Capitation indicator (KBK) influencing FKTP monthly income.